Mixed germ cell tumour of ovary presenting as pregnancy: a rare presentation - Mahadevappa, Kavita; Prasanna, Naveen; Bembalgi, Shobha; Giriyan, Sujata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Malignant mixed germ cell tumour of the ovary containing embryonal carcinoma and choriocarcinoma is a very rare entity. These tumours can present as precocious puberty or menstrual irregularities in adolescent girls. Here we report a case of 22 year old lady who presented as 5 months pregnancy in antenatal clinic. MRI Imaging and tumour markers revealed malignant ovarian tumour. Patient underwent surgicopathological staging and was found to have malignant mixed germ cell tumour stage IIIB, comprising of both choriocarcinoma and embryonal carcinoma components. Patient received one cycle of chemotherapy and was called for follow up. Mixed malignant germ cell tumour of the ovary is a highly aggressive neoplasm that can present in advanced stage. A high clinical suspicion is needed in patients presenting with pelvic mass associated with menstrual irregularity or amenorrhoea in adolescent and young women.